(x-67)=x*1.47

Simple and best practice solution for (x-67)=x*1.47 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-67)=x*1.47 equation:


Simplifying
(x + -67) = x * 1.47

Reorder the terms:
(-67 + x) = x * 1.47

Remove parenthesis around (-67 + x)
-67 + x = x * 1.47

Reorder the terms for easier multiplication:
-67 + x = 1.47x

Solving
-67 + x = 1.47x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1.47x' to each side of the equation.
-67 + x + -1.47x = 1.47x + -1.47x

Combine like terms: x + -1.47x = -0.47x
-67 + -0.47x = 1.47x + -1.47x

Combine like terms: 1.47x + -1.47x = 0.00
-67 + -0.47x = 0.00

Add '67' to each side of the equation.
-67 + 67 + -0.47x = 0.00 + 67

Combine like terms: -67 + 67 = 0
0 + -0.47x = 0.00 + 67
-0.47x = 0.00 + 67

Combine like terms: 0.00 + 67 = 67
-0.47x = 67

Divide each side by '-0.47'.
x = -142.5531915

Simplifying
x = -142.5531915

See similar equations:

| 6d+(5.5)=2d-(6.5) | | 6d+5.5=2d-(6.5) | | 6d+5.5=2d-6.5 | | 17x+3=17x | | -33*1/5 | | 288/6 | | (3/4)-(9/12) | | 68(x-3)=-2x+35.6 | | 10x+5y+15z= | | (x-1)(x+5)-(x+2)(x-3)=3(1+5x) | | -8x-18=6 | | (3/4)-(3/12)= | | y-21=2(x-9) | | m-8-2=4 | | TanX=27/32 | | 3/4-3/12 | | 5(3x-1)+7=2-(5x-3) | | F(x)=4x^2+7x-6 | | 5(2x+1)=3x+19 | | -7x^2+34x+5= | | x+2(80-x)=100-4(25-x) | | 6x/(x^2) | | g^2+4g-32=9 | | 5x=6x-14+12 | | y/7=2/x | | 84/(7) | | 9x/4=15 | | 9x/4=`15 | | 3x+5(2x-12)=5 | | 4x+3y=z | | 8+5x=7x+2 | | -2+10x=8x+1 |

Equations solver categories